Crew cutting rock on a steep slope of Tunnel Mountain to construct grade of the White Pass & Yukon Railway, Alaska, 1898. - Barley, H. C.
Caption on image: "Cutting the grade on Tunnel Mountain" PH Coll 246.139 See also PH Coll 296.16 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number